THE ROLE OF THE GOVERNMENT AND TIK TOK IN PROVIDING LEGAL PROTECTION FOR CREATORS AGAINST COPYRIGHT INFRINGEMENT FOR RE-SHOWING CINEMATOGRAPHIC WORKS ON THE TIK TOK APPLICATION - Agustin, sasmitha; Mahanani, Anajeng Esri Edhi (JOSAR (Journal of Students Academic Research), 2024)
Based on the Copyright Law, cinematographic works are defined as creations in the form of moving images, including documentary films, advertising films, reportages or story films made with scenarios, and cartoon films. In this modern era, the entertainment industry is also experiencing modernization in its broadcast media. Now you can easily find legal applications for enjoying cinematographic works on smartphones. Apart from using this convenience in a positive way, it turns out that there is still a gap for someone to commit a crime from the existing convenience, such as copyright infringement on cinematographic works. If this violation has occurred, what about legal protection for the creator of his work? The research used in this research is normative legal research or doctrinal law. Normative legal research is a type of legal research whose process is based on the logic of legal science from its normative side. In this research, researchers took a legislative approach by analyzing the relationship between one legal regulation and other regulations related to the problems that occurred. The results of this research explain the forms of copyright infringement against re-displays of cinematographic works on the Tik Tok application and the role of the government and Tik Tok in providing legal protection for creators against copyright violations for re-displays of cinematographic works on the Tik Tok application.